PEMANFAATAN CITRA SATELIT UNTUK IDENTIFIKASI PERKEMBANGAN KAWASAN TERBANGUN KOTA PADANG PANJANG TAHUN 2009 DAN 2019 - khairun nisa; Febriandi Febriandi (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This research was conducted in the city of Padang Panjang which aims to determine the development of the area of ​​the built-up area in the City of Padang Panjang in 2009 and 2019, to determine the factors that influence the development of the built-in area and the direction of development in the area of ​​Padang Panjang City and to see the accuracy of Landsat 5 imagery. TM and Landsat 8 OLI / TIRS in identifying the built area of ​​Padang Panjang City. The method used in this research is descriptive with a quantitative approach and the data used are primary data and secondary data. The built area was obtained from Landsat 5 TM and Landsat 8 OLI imagery using the NDBI Alogarithm method. The results of the identification of land changes built from 2009 to 2019 show an additional area of ​​247.82 hectares and in 2019 an area of ​​305.08 hectares has increased to 57.26 hectares. Image accuracy test is performed using confusion matrix (comparison of image interpretation with field conditions) with an accuracy rate of 88.43%.